Revenge Porn dan Dampak Psikologis Pada Korban: Kajian Psikologis dan Tinjauan Singkat Hukum - Sintya Mauliddina; Yusti Probowati Rahayu; Ajuni Ajuni; Mary Philia Elisabeth (Dinasti Research, 2024)
he development of technology brings great benefits but also opens a loophole for cybercrime. Cases of revenge porn, which is the dissemination of pornographic content without consent, are becoming increasingly troubling. Data from Komnas Perempuan Indonesia shows a sharp spike in cases of gender-based violence. This study describes the phenomenon of revenge porn, illustrating the significant psychological impact on victims. This study uses a literature study method conducted using 8 journals from 2016-2022. Through interviews with survivors as additional data, it was found that the impact of revenge porn involves psychological, social isolation, and economic loss, resulting in victims losing basic needs and psychological needs in Maslow's hierarchy of needs. The TPKS Law is considered less capable of providing punishment that is worthy of what the victim received. The psychological impact felt indirectly takes away the pre-existing hierarchy of needs and slowly destroys part of the victim's life.